A systematic review of the knowledge, attitudes and perceptions of health and social care professionals towards people with learning disabilities and mental health problems. - Ee, Jonathan; Stenfert Kroese, Biza; Rose, John (British Journal of Learning Disabilities, 2022)
Accessible Summary: Many people with learning disabilities need mental health services at some point in their lives.This paper looks at how health and social care professionals (e.g. doctors, nurses and psychologists) think about people with learning disabilities who also have mental health problems.The research shows that health and social care professionals who do not work in learning disability services are not comfortable working with people with learning disabilities because they do not know enough about them and have not had proper training.Health and social care professionals also have negative views of people with learning disabilities. They prefer it if a specially designed mental health service takes on the work with people with learning disabilities.Having more training can help health and social care professionals to become more confident in this work. Background: People with learning disabilities have poorer access to mental health services. It is important for health and social care professionals to have adequate knowledge and skills combined with positive attitudes to work with this population. This review focuses on the knowledge, attitudes and perceptions of health and social care professionals who provide mental health services to people with learning disabilities. Method: A systematic literature search was carried out to identify quantitative studies published in the English language between 2006 and 2020. Results: Thirteen studies were identified that met the inclusion criteria. The studies identified a lack of knowledge and competency among health and social care professionals to address the mental health needs of people with learning disabilities. Health and social care professionals in these studies viewed people with learning disabilities are more vulnerable and suggested specialist mental health services to cater to their specific mental health needs. Conclusions: Health and social care professionals appear to hold negative views of people with learning disabilities, which adversely influences their willingness to work with them. It is recommended that health and social care professionals receive more training opportunities to increase their skills and develop confidence in providing services to this population.